Tools to Develop End-User Programming Skills from Primary School to Higher Education - Takács, Viktor László; Bubnó, Katalin; Szilágyi, Róbert (International Journal of Engineering and Management Sciences, 2018)
Some years ago at the MIDK2013 Conference [16] we presented a concept regarding the use of a new generation of computer programming novice languages (in fact, an environment, called ‘block languages’). We showed how we imagine the use of this kind of language for different ages and at different levels of education. Now we would like to present the results of our projects related to this concept and our psychological and pedagogical experiences. Furthermore we would like to present further tools to develop end-user programming skills from primary school to higher education.